Natural area tourism : ecology, impacts and management - Newsome, David; Moore, Susan ; Dowling, K. Ross (India, 2006)
This book was born out of an individual and collective passion for the natural envi-ronment. We are all environmental scientists who have spent a great part of our lives travelling in, researching about, and teaching for, a greater understanding of the global environment. Therefore it was only natural that at some stage we should wish to share our knowledge of, and enthusiasm for, natural areas and this has manifested itself through tourism. One of us has been a tour guide to national parks and wilderness areas for 25 years, another has been a natural area manager for more than a decade, while all of us have led field trips to natural areas as part of our tertiary teaching. We love the environment and believe that through tourism to natural areas people will be stirred within to act positively for their own environment upon their return to the predominantly urban areas from which they came.
Keywords: Ecological Tourism; Natural Area Touris; Tourism industry